Reliving small pleasures of life in Polish - Skibińska, Elżbieta (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
Philippe Delerm’s book La première gorgée de bière et autres plaisirs minuscules (1997) consists of thirty-four mini-stories that form an inventory of small joys, of everyday moments that seem to be tiny, fleeting celebrations. Some of these stories are related to the pleasures of the table (food and table habits or routines). This study presents the book’s “culinary scenes” and the way they are rendered in the Polish translation (Pierwszy łyk piwa, 2004). The aim of this comparison is to see whether the translation makes it possible for the Polish audience to feel the connivance or complicity inscribed in Delerm’s text regarding food, and to evaluate to what extent reading Pierwszy łyk piwa can be part of the art of “surviving” (serving as an escape) in difficult moments such as the 2020 pandemic, a global experience that has upset our daily lives.